Lead Isotope Analysis of Pewter Mounts from the Viking Ship Burial at Gokstad: on the Origin and Use of Raw Materials. (11th December 2015) - Pedersen, U.; Andersen, T.; Simonsen, S.; Erambert, M.
Abstract : Lead isotope analysis was combined with an investigation of style and technology in a study of pewter mounts from the Viking ship burial at Gokstad, Norway. The different methods reinforced one another and yielded a detailed picture of a ninth‐century working process, demonstrating the potential of applying lead isotope analysis to artefact studies independent of the question of provenance. They provided evidence of the mounts being produced as a set, and signs of mixing demonstrate that it is important to be cautious when discussing provenance. England and Melle, France are indicated to be the most likely origin of the lead.